COVID-19 biobank: features of the cytokine profile - N. N. Sushentseva; O. S. Popov; S. V. Apalko; A. Yu. Anisenkova; S. V. Azarenko; K. V. Smantserev; D. N. Khobotnikov; T. V. Gladysheva; E. V. Minina; S. V. Strelyukhina; S. P. Urazov; D. Pavlovich; et al. (Кардиоваскулярная терапия и профилактика, 2020)
Aim. Using a collection of samples from the biobank ofCityHospital № 40 ofSt. Petersburg, to study the cytokine profile in patients with coronavirus disease 2019 (COVID-19) and sepsis, in comparison with patients with abdominal inflammation and septicemia.Material and methods. The study included serum samples from 181 patients with sepsis and COVID-19 (127 patients with a diagnosis confirmed by polymerase chain reaction (PCR); 54 patients with a negative PCR test, but with a characteristic computed tomographic lung performance) and 47 patients with abdominal sepsis. The content of cytokines was determined using a multiplex immunofluorescence analysis based on the Luminex xMAP technology using the HCYTOMAG60K panel — a soluble CD40 ligand (sCD40L), interleukin-1α (IL-1α), interleukin-1β (IL-1β), interleukin 6 (IL-6), interleukin 8 (IL-8), monocyte chemoattractant protein 1 (MCP-1), tumor necrosis factor alpha (TNFα), vascular endothelial growth factor (VEGF). Other laboratory parameters (C-reactive protein (CRP), ferritin, procalcitonin) were taken from patient records. Normality of distribution was assessed by the Shapiro-Wilk test. To compare groups, the Mann-Whitney test for independent samples, Wilcoxon test for dependent samples, and the Kruskal-Wallis test with Bonferroni correction for multiple comparisons were used.Results. In patients with sepsis and COVID-19 infection, no differences in the concentrations of cytokines, ferritin and CRP were found between the groups with detected and not detected virus by PCR test. Based on this, this group was considered homogeneous when studying the cytokine profile. It was shown that in patients with sepsis and COVID-19, significantly higher levels of sCD40L (p<0,0001) and VEGF (p=0,037) and relatively low levels of CRP (p<0,0001), IL-6 (p<0,0001), IL-8 (p<0,0001), TNFα (p<0,00058).Conclusion. These results indicate that sepsis in patients with COVID-19 courses with less elevation in inflammatory cytokine than in abdominal sepsis. At the same time, a critically high level of sCD40L indicates the significant endothelial damage.